Human papillomavirus genotyping using next generation sequencing (NGS) in cervical lesions: Genotypes by histologic grade and their relative proportion in multiple infections. - Jorge Alejandro Basiletti; Joan Valls; Tomás Poklépovich; María Dolores Fellner; Maryluz Rol; Rafael Alonso; Rita Mariel Correa; María Celeste Colucci; Mercedes Rodríguez de la Peña; Paula Gabriela Falabella; Agustina Saíno; Josefina Campos; et al. (PLoS ONE)
Sensitive and specific genotyping of human papillomaviruses (HPVs) is critical for the surveillance and monitoring of the vaccine effectiveness. Here, HPV genotypes were identified in 137 cervical samples with different histology (79 ≤CIN1 and 58 CIN3+) using Nested-PCR followed by Next-Generation sequencing (NGS) and relative proportions for each genotype in multiple infections were computed. All samples had been previously genotyped by PCR-Reverse Blotting Hybridization (PCR-RBH) thus allowing for a concordance analysis between both techniques. Multiple infections were present in 85% of ≤CIN1 cases compared to only 41% in CIN3+ cases (p<0.001). Among ≤CIN1 cases a towering genotypic diversity was observed, considering both low (LR-) and high risk (HR-) HPV genotypes; while among CIN3+, diversity was lower, HR-HPVs prevailing in most cases, especially HPV16. Furthermore, the predominance of HR-HPV genotypes in the proportions identified in each sample was higher in CIN3+ cases [(HPV16 (62.5%), followed by HPV31 and HPV58 (8.3% each)], than in ≤CIN1 cases [(HPV16 (17.7%), followed by HPV52 (14.7%) and HPV31 (10.3%)]. Agreement between PCR-RBH and NGS was higher than 90% for all genotypes (with an overall Kappa of 0.7), even though NGS identified eighty-nine positive results for HPV genotypes that had not been detected by PCR-RBH, evidencing its greater sensitivity. These results suggest that a reduction in genotypic diversity and/or an increase in the relative proportion of HR-HPVs in multiple infections can be considered as a biomarker for the potential risk of malignant progression.